2015
DOI: 10.1109/tbme.2015.2477095
|View full text |Cite
|
Sign up to set email alerts
|

Objective Assessment of Upper Limb Mobility for Post-stroke Rehabilitation

Abstract: The assessment of the limb mobility of stroke patients is an essential part of poststroke rehabilitation. Conventionally, the assessment is manually performed by clinicians using chart-based ordinal scales, which can be subjective and inefficient. By introducing quantitative evaluation measures, the sensitivity and efficiency of the assessment process can be significantly improved. In this paper, a novel single-index-based assessment approach for quantitative upper-limb mobility evaluation has been proposed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 38 publications
0
64
0
Order By: Relevance
“…For example, Saraee et al [137] used the DTW distance and speed ratio of key body joints for an exercise to directly evaluate the quality of performance with respect to reference template sequences. In [138] and [123], movement quality scores were derived by scaling the DTW distance values in the [0, 1] range. In the former, the DTW distance errors were scaled by the lower bound and upper bound, based on a scoring function introduced in [142].…”
Section: A) Distance Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Saraee et al [137] used the DTW distance and speed ratio of key body joints for an exercise to directly evaluate the quality of performance with respect to reference template sequences. In [138] and [123], movement quality scores were derived by scaling the DTW distance values in the [0, 1] range. In the former, the DTW distance errors were scaled by the lower bound and upper bound, based on a scoring function introduced in [142].…”
Section: A) Distance Functionsmentioning
confidence: 99%
“…The studies in the literature based on evaluation using distance functions reported a high correlation between patient's performance and clinicians' evaluation. For instance, DTW-based evaluation achieved high posture monitoring accuracy (91.9%) and exercise monitoring accuracy (95.2%) in comparison to clinicians' annotated rehabilitation data [55], high correlation with the Brunnstrom stages of recovery (86% at p<0.001) [138], and high predictive score accuracy (80%) [57] in comparison to clinical evaluation.…”
Section: A) Distance Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterward, two advanced classification techniques were applied to distinguish hand movements: k-nearest neighbor (k-NN) and SVM. These types of techniques have been used previously to classify signals for stroke rehabilitation (Munoz et al, 2014;Zhang et al, 2015). We provide links to our software that implements these algorithms in Supplementary Material.…”
Section: Improving the Classification Accuracy Of Epoc+ And Acticap Dmentioning
confidence: 99%
“…The Brunnstrom approach is focused on the progressive development of the motion synergic pattern during the rehabilitation process and divides the motor recovery into six stages from the period of complete flaccidity to the disappearance of spasticity when the patient is able to perform near-normal to normal movement. The simplicity makes the Brunnstrom classification one of the most favorable measures as a repetitive follow-up test during rehabilitation program [9,10].…”
Section: Brunnstrom Recovery Stages (Brs)mentioning
confidence: 99%